Case report: Paroxysmal nocturnal hemoglobinuria presenting with hemorrhagic esophageal varices - Du, Runsen; Zheng, Lihua; Liu, Peng; Zhao, Yaheng; Yang, Yan; Zhang, Lei; Zhao, Zengren (Frontiers in Medicine, 2023)
We report the case of a woman who was cured of hemorrhagic esophageal varices caused by Paroxysmal nocturnal hemoglobinuria (PNH) through the treatment of Transjugular intrahepatic portosystemic shunt (TIPS). PNH complicated by portal vein and visceral veins thrombosis without hepatic veins is extremely rare, and as such, may be easy to be treated incorrectly due to lack of awareness. Hemorrhagic esophageal varices due to PNH with PVT have been reported in 1 case in 1974, and We report the second.